Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.3892/ijo.2014.2680
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200 family members and ZEB2 are associated with brain metastasis in gastric adenocarcinoma

Abstract: Abstract. Although the incidence of brain metastasis in gastric cancer is relatively low, its prevalence may increase with improved therapy and longer survival tumors. The molecular mechanisms underlying brain metastases are not well understood. To gain insight into the mechanism of brain metastasis, we studied differences in microRNA (miRNA) expression levels in 8 cases of matched primary gastric adenocarcinoma and brain metastatic adenocarcinoma using the Illumina microRNA microarray chip. We identified 6 up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 30 publications
(38 reference statements)
1
24
0
Order By: Relevance
“…Loss of E-cadherin is generally accepted to be a hallmark event of the EMT process, during which epithelial cells undergo profound phenotypic modification and lack of polarity to turn into mesenchymal cells, reducing contact with surrounding cells or matrix as well as acquiring the ability of migration and invasion. of brain metastasis or small sample size due to low incidence (39). However, this finding might support the theory of MET process that anchors circulating cancer cells to metastatic organs, although the effect of this in metastatic dissemination is still under debate (40).…”
Section: Epithelial-mesenchymal Transition and Gastric Cancersupporting
confidence: 51%
“…Loss of E-cadherin is generally accepted to be a hallmark event of the EMT process, during which epithelial cells undergo profound phenotypic modification and lack of polarity to turn into mesenchymal cells, reducing contact with surrounding cells or matrix as well as acquiring the ability of migration and invasion. of brain metastasis or small sample size due to low incidence (39). However, this finding might support the theory of MET process that anchors circulating cancer cells to metastatic organs, although the effect of this in metastatic dissemination is still under debate (40).…”
Section: Epithelial-mesenchymal Transition and Gastric Cancersupporting
confidence: 51%
“…According to recent studies [39-41], ZEB1 plays a valuable role and has clinical significance in peritoneal dissemination of gastric cancers, and is a promising target molecule for prognosis and therapy. More recently, ZEB2 has been garnering similar attention for its potential in gastric [42, 43] and other cancers [44, 45]. Indeed, we found that siRNA-mediated downregulation of ZEB1 or ZEB2 successfully inhibited peritoneal dissemination in our own orthotopic 58As9 tumor models (Takei Y, et al, unpublished results).…”
Section: Discussionmentioning
confidence: 52%
“…Investigations of miRNAs as biomarkers have employed the expression profiling of non-invasive samples such as body fluids [3].Various studies on epithelial malignancies have shown encouraging results on various fronts [4]. Aberrant expression of the miR-200 family has been linked to the occurrence and development of various types of malignant tumors [5] including hepatocellular carcinoma [6], colon cancer [7],breast cancer [8], ovarian cancer [9], lung cancer [10], gastric cancer [11,12], osteosarcoma [13], etc. Although miR-200 family members are thought to play roles in tumorigenesis, their functions in carcinogenesis are tumor specific, and the underlying mechanism of action still remains elusive [14].…”
Section: Introductionmentioning
confidence: 99%